Anxiety and depressive symptoms effects on cortisol trajectories from pregnancy to postpartum: Differences and similarities between women and men - Conde, Ana (2021)
Anxiety and depressive symptoms may influence cortisol trajectories in women and men during pregnancy and the postpartum period. Using a multilevel approach, anxiety and depressive symptoms effects on 24-hour urinary free cortisol trajectories from the 2nd trimester to 3-months postpartum were examined in a sample of 66 women and 65 men with no known psychosocial or medical risk (N = 131; 33 (50%) of them were couples that participated in the same assessment waves). Results showed that both anxiety and depressive symptoms influence women's and men's cortisol trajectories from mid-pregnancy to 3-months postpartum. Women with high depressive symptoms and men with high anxiety or high depressive symptoms exhibited less accentuated variations in the 24-hour urinary free cortisol trajectories compared with women with low depressive symptoms and men with low anxiety or depressive symptoms, respectively. These effects were significant for women's cortisol trajectories from the 2nd to the 3rd pregnancy trimester and for men's cortisol trajectories throughout the entire period. The effect of anxiety and depressive symptoms on HPA axis functioning and cortisol production during pregnancy and postpartum, seems to be sex-specific. Reproductive-related alterations (associated with gestation, parturition and lactation) in women's HPA axis functioning may explain these sex-specific effects.